Assessing urban public transportation, legislative and institutional framework in federal territory of Kuala Lumpur / Noor Ashikin Abd Rahman - Abd Rahman, Noor Ashikin (2019)
The trends in transportation have been changing and will continue to change over the years. Urban dwellers in developing countries require and demand for mobility and accessibility at the same growth rate of these urban areas. Often, this demand is accommodated by the increased number of private vehicles. Development of a country is closely linked with the transportation system facilities thus will have a positive impact on the economic growth and social fabric of a country. The traffic issues are always associated with private vehicles especially in any developing cities such as the Federal Territory of Kuala Lumpur. At present, the traffic problems in Malaysia are resulted from ineffective public transport system which is not methodically integrated from one place to another, therefore, forcing the people to use private vehicles for daily uses. An integrated and comprehensive approach is required as it enhances the regulatory framework, planning structure and level of services delivered. The notions for this topic were developed from issues regarding institutional framework in terms of effective delivery for urban public transport. Although the current urban public transport in Klang Valley has improved, there are still issues regarding this matter. This research, therefore, aims to evaluate the delivery of public transportation through legislative and institutional framework in the Klang Valley especially for the Federal Territory of Kuala Lumpur. This research also emphasises on the importance of public transportation policies and legislation, the role of Government Agencies and Statutory Body involved in urban public transport and to make recommendations in order to improve the current institutional framework of urban public transportation. Expert Interviews were conducted to examine the role of agencies related to urban public transport and the implementation of the public transport policies. Structured Interviews were exercised in gathering primary data from related agencies and the interviews were conducted through targeted agencies involving seven (7) agencies in which samples were determined through a structured technique, namely, Purposive Sampling. The collected data were later analysed using the Descriptive Policy Analysis and Content Analysis.